2017
DOI: 10.3390/ijms18050997
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Optical and Mechanical Properties of Chitosan–Starch Films with Natural Extracts

Abstract: Natural extracts possess several kinds of antioxidants (anthocyanins, betalains, thymol, carvacrol, and resveratrol) that have also demonstrated antimicrobial properties. In order to study these properties, extracts from cranberry, blueberry, beetroot, pomegranate, oregano, pitaya, and resveratrol (from grapes) were obtained. Growth inhibition tests of mesophilic aerobes, coliforms, and fungi were conducted in films prepared from the extracts in accordance with Mexican Official Norms (NOM). Optical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 33 publications
7
50
0
Order By: Relevance
“…Thus, they are difficult to compare with other starch‐chitosan materials. For instance, values of maximum Tan δ have been obtained from starch‐chitosan materials (50 wt.% of each polysaccharide and approximately 6.2 wt% of plasticizer) at around 185 °C and also at around 89 °C (66 wt% of starch and 33 wt% of chitosan, considering 10 wt% of plasticizer). Thus, the polymer starch‐chitosan (5–95 wt% and 1 wt% of plasticizer) in this research presented a Tg around 104 °C, and as mentioned earlier, this value tended to decrease in the samples with keratin.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they are difficult to compare with other starch‐chitosan materials. For instance, values of maximum Tan δ have been obtained from starch‐chitosan materials (50 wt.% of each polysaccharide and approximately 6.2 wt% of plasticizer) at around 185 °C and also at around 89 °C (66 wt% of starch and 33 wt% of chitosan, considering 10 wt% of plasticizer). Thus, the polymer starch‐chitosan (5–95 wt% and 1 wt% of plasticizer) in this research presented a Tg around 104 °C, and as mentioned earlier, this value tended to decrease in the samples with keratin.…”
Section: Resultsmentioning
confidence: 99%
“…CH is a linear polysaccharide that consists of a low acetyl substituted form of chitin and a natural carbohydrate copolymer. CH offers several advantages such as biodegradability, broad availability, and non-toxicity [8]. CH also has good anti-fungal activity against several postharvest pathogens, particularly the grey mold that is one of the main causes of strawberry deterioration and postharvest decay [9].…”
Section: Introductionmentioning
confidence: 99%
“…Each film blend was stirred for 5-10 min, and later, the resulting blend was verted in a polystyrene tray. Finally, the films were dried at 25 • C for 15 days [13]. For the films with natural extracts, two fixed quantities (0.4 and 1.6 mL) of each extract were added into the polymer solution (corresponding to 0.5% and 2% of the total blend weight).…”
Section: Synthesis Of Filmsmentioning
confidence: 99%
“…This is confirmed by the research of Rongsayamanont et al (2017), who indicated the stability of biosorbents (composed by lipopeptides, glycerol, and palm oil) at a pH media range of 4-10 (using substances such as deionized water, alkaline water at pH 9, methanol, ethanol, dimethyl sulfoxide, acetone, chloroform, and hexane, it pointed the sorption capacity of biomaterials in acidic and alkaline media) without losing the film stability [23]. It is important to remark that the addition of higher quantities of extract gives the materials a lower pH value [13]. This fact allows the films to have a higher affinity and effectivity in acid media.…”
Section: Ph Measurement Of Watermentioning
confidence: 99%